2007
DOI: 10.1074/jbc.m707233200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cϵ Regulates γ-Aminobutyrate Type A Receptor Sensitivity to Ethanol and Benzodiazepines through Phosphorylation of γ2 Subunits

Abstract: Ethanol enhances ␥-aminobutyrate (GABA) signaling in the brain, but its actions are inconsistent at GABA A receptors, especially at low concentrations achieved during social drinking. We postulated that the ⑀ isoform of protein kinase C (PKC⑀) regulates the ethanol sensitivity of GABA A receptors, as mice lacking PKC⑀ show an increased behavioral response to ethanol. Here we developed an ATP analog-sensitive PKC⑀ mutant to selectively inhibit the catalytic activity of PKC⑀. We used this mutant and PKC⑀ ؊/؊ mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 37 publications
3
106
0
Order By: Relevance
“…As shown in Figure 4A, PKCε phosphorylated the intracellular Na v 1.8/L3 loop at a rate similar to phosphorylation of the major intracellular loop of the GABA A γ2S subunit, which contains a PKCε phosphorylation site at S327 (9). Similar to GABA A γ2S, the Na v 1.8/L3 loop was phosphorylated to a maximal stoichiometry of 0.95 ± 0.08 (n = 3), suggesting that it is a true PKCε substrate.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 4A, PKCε phosphorylated the intracellular Na v 1.8/L3 loop at a rate similar to phosphorylation of the major intracellular loop of the GABA A γ2S subunit, which contains a PKCε phosphorylation site at S327 (9). Similar to GABA A γ2S, the Na v 1.8/L3 loop was phosphorylated to a maximal stoichiometry of 0.95 ± 0.08 (n = 3), suggesting that it is a true PKCε substrate.…”
Section: Figurementioning
confidence: 99%
“…(A) The top 2 panels show an autoradiogram of phosphorylated intracellular L3 loop (p-L3) and a scanned image of a Coomassie blue-stained gel before autoradiography (L3). The bottom 2 panels are an autoradiogram and gel of PKCε phosphorylation of the large intracellular loop of the GABAA γ2 subunit (p-γ2s), a known PKCε substrate (9). (B) An autoradiogram and Western blot with anti-6xHis antibody, showing that PKCε phosphorylation of the NaV1.8 L3 loop was substantially reduced by alanine substitution at S1452 but not at T1437.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that PKC epsilon is necessary for ethanol's modulatory effects on GABA A receptors (Besheer et al 2006). Because no drug was available that selectively inhibited PKC epsilon activity over other PKC isoforms, the authors used a chemical strategy to generate an ATP analogue-sensitive PKC epsilon mutant to selectively inhibit catalytic activity of PKC epsilon (Qi et al 2007). Using this mutant, they showed that PKC epsilon affects GABA A receptors by phosphorylating the g2 subunit, thereby affecting receptors with the a1b2g2 subunit composition, an abundant variant in brain.…”
Section: Candidate Genesmentioning
confidence: 99%
“…Messing and co-workers have shown that activity of the epsilon subunit of protein kinase C (PKC) is necessary for EtOH potentiation of γ2-subunitcontaining GABA A receptors expressed heterologously in a mammalian cell line (Qi et al 2007). This PKC action appears to involve phosphorylation of a specific serine residue on the γ2 subunit.…”
Section: Ligand-gated Ion Channels and Postsynaptic Ethanol Effectsmentioning
confidence: 99%